LGBTQ+ librarianship in the 21st century : emerging directions of advocacy and community engagement in diverse information environments - Mehra, Bharat (Advances in librarianship., 2019)
Libraries are at the heart of many of the communities they serve. Increasingly, it is important for them to adjust to serve minority groups, including LGBTQ+ communities. This collection presents original scholarship on the emerging directions of advocacy and community engagement in LGBTQ+ librarianship.